THE ISSUES AND CHALLENGES OF PRIVATE RETIREMENT SCHEME IN AIA PENSION AND ASSET MANAGEMENT SDN. BHD. - Wan Ahmad Fathijaya Ningrat , Wan Luqmanul Hakim; Kamal , Dr. Asiah; Hasan, Dr. Norzuraida; Mustafa@Busu , Zanirah (Journal of Islamic, Social, Economics and Development, 2024)
A Private Retirement Schemes (PRS) is a voluntary, long-term savings and investment plan created to help individuals increase their retirement funds. The PRS aims to expand the options accessible to all Malaysians, regardless of employment status, to improve their retirement funds under a structured and organized framework. This study was conducted through interviews to obtain data from the general manager of AIA Pension and Asset Management Sdn. Bhd. (APAM) which is used to obtain information from informants orally. The researcher used semi-structured interviews in which the researcher incorporated a set of open-ended questions that had been set by giving the researcher the opportunity to explore further topics related to issues and challenges in PRS. This research explores the issues and challenges of the PRS offered by APAM with a focus on implementation related to the scheme. Despite their potential to provide secure and structured retirement savings, SPS face several issues, including investment performance due to market volatility, low financial literacy and awareness among Malaysians and lack of competent staff. The study identifies key areas for improvement and offers strategic recommendations to increase the effectiveness and appeal of PRS. In this article include funding important public education initiatives, reducing administrative and management costs and fostering strategic partnerships. By addressing these issues and challenges, APAM can increase participation rates and ensure contributors reach their retirement goals, thereby strengthening the overall stability and attractiveness of their SPS offering.